Determination of mean values of the number, perimeter and area of CD34-positive of rosacea vessels and evaluation of VEGF expression in skin biopsy specimens of patients with vascular forms. - О. А. Starostina (Medičnì Perspektivi)
Rosacea is characterized by marked involvement of the central face with transient or persistent erythema formation, telangiectasias, inflammatory papules and pustules and hyperplasia of the connective tissue. The formation of telangiectasia of the surface and intermediate sections of the dermis is an important chain of pathogenesis of vascular forms of rosacea. Modern literature sources allow to attribute this disease to the group of angioproliferative diseases, which are based on the activation of the inflammation and angiogenesis. This leads to the need of studing the mechanisms of vascularization due to growth factors of the vascular components or their receptors in rosacea. The aim of the study was to calculate the mean values of the perimeters and areas of CD34-positive vessels, to evaluate the intensity of expression of the VEGF marker in the skin biopsies of patients with vascular forms of rosacea and to determine the possible dependence of these parameters on the age of the patients. In the work, an immunohistochemical analysis of the material of 11 patients aged 21 to 63 years (mean 40,0±12,49, median 36 years) with a clinical diagnosis of the vascular form of rosacea was performed. Branching, dilatation and induration of the capillary mesh were the typical changes in the dermis in vascular forms of rosacea. which were observed throughout the length of the incisions with an increase in the direction "from the top down", especially around the sebaceous glands and hair follicles. It was established that the mean values of the number, perimeters, and areas of CD34-positive vessels in rosacea biopsy specimens, as well as the levels of VEGF expression, were significantly higher than those of healthy skin (all p<0,05).